Análise do comportamento e o negro no Brasil: avaliação de um procedimento de formação de classes equivalentes de estímulos relacionadas ao viés racial em adultos negros e brancos - Jardim, Pedro Henrique (2018)
As a social science, Behavior Analysis has the technology to study cultural practices related to racial issues. This study aimed to evaluate the effects produced by a negative racial bias reduction procedure related to black people. Seventeen participants, 10 blacks and seven whites, who filled a self-declaration questionnaire, were selected. The activity consisted of an arbitrary matching-to-sample training. Before it, the participants trained the relationship between thumb up and thumb down, and stimuli with hit and miss functions. They also performed a pretraining, in which a software (IRAP) was applied, in order to measure the latency of responses for each group of stimuli related to figures of white and black people and to verify if the responses indicated negative racial bias because of the time to respond. In the procedure of stimulus equivalence class formation related to the reduction of the negative bias itself, three relations were trained: (a) between thumb up/thumb down and abstract figures (AB); (b) between abstract figures and black people (BC); and (c) both (ABBC), simultaneously. After each training, tests of symmetry, transitivity and equivalence (AC and CA) were performed. A complementary test (AC3), in which another comparison stimulus was added (white people), was also applied. Finally, IRAP was used again in order to verify if there were changes after training. Initial results indicated that participants were not biased towards black people. However, the training was effective for stimulus equivalence class formation, with the exception of one participant. The application of IRAP at the end indicated varied results. It is recommended that future researches verify whether a white experimenter would achieve distinct results and whether stimuli of both black men and women have the same effect in participants as well as testing other methods of verifying implicit racial bias